College students’ exercise experience and aggression during COVID-19: A chain mediating model - Jiang, Qi (Frontiers in Psychology, 2022)
Aim: This study aimed to explore to how exercise experience affects the aggression of college students and the mediating effects of mood and exercise attitude in COVID-19. Methods: A questionnaire survey (The Subjective Exercise Experience Scale (SEES); Profile of Mood State (POMS); Exercise Attitude Scale; Aggression Questionnaire (AQ)) was conducted among 1,006 college students. Results: Exercise experience had a significant effect on aggression. The direct effect of exercise well-being was not significant, but indirectly affected the aggression through independent mediation and chain mediation of mood and exercise attitude. The direct effect of exercise distress was not significant, but indirectly affected the aggression through independent mediation and chain mediation of mood and exercise attitude. Conclusion: Mood and exercise attitude are powerful factors to alleviate the impact of exercise experience on aggression during the pandemic. Actively adjusting the mood and exercise attitude from a cognitive perspective may be an effective way to promote college students’ physical exercise and reduce aggression.